(untitled) (Annals of Medical Research, 2021)
Aim: Previous studies have shown cyclodextrins bind to a variety of medications. The hypothesis in our study is to determine whether or not sugammadex interacts with the lipophilic medication of ketamine to shorten the effect duration and ensure earlier recovery. Material and Methods: The study used 24 adult male Sprague-Dawley rats. Rats were randomly divided into 4 equal groups. Each rat was administered 75 mg/kg ketamine intraperitoneal (ip) bolus and then in the fifth minute rats was administered sugammadex at appropriate doses for their group through the lateral vein in the tail. Group C (control group) were administered 15 mL/kg physiologic serum (PS) (n=6), Group Sgdx 16 were administered 16 mg/kg sugammadex (n=6), Group Sgdx 100 were administered 100 mg/kg sugammadex (n=6) and Group Sgdx 1000 were administered 1000 mg/kg sugammadex (n=6). The heart rate, respiratory rate and recovery durations of the rats were recorded. Results: The recovery duration in the Sgdx 100 group was statistically significantly shorter compared to the control group (p=0.026), while the recovery duration in the Sgdx 1000 group was statistically significantly shorter than the control group (p0.001) and the Sgdx 16 group (p=0.015). Heart rate was statistically significantly low in the Sgdx 1000 group compared to the control group (p0.05). Respiratory rates were similar. Conclusion: Our study showed that 100 mg/kg and 1000 mg/kg sugammadex doses significantly shortened recovery. We conclude that there is a need for more research about the interaction between ketamine and sugammadex.